The third day, the frost - Marsden, John, 1950- (London : Quercus, 2012)
Ellie and her friends, a small band of teenagers trying to survive in the Australian countryside, continue to resist the enemies who have invaded their country.
Keywords: Courage -- Juvenile fiction; Death -- Juvenile fiction; Friendship -- Juvenile fiction; Guerrillas -- Australia -- Juvenile fiction; War stories; Wilderness survival -- Juvenile fiction; Survival -- Fiction; War -- Fiction; Australia -- Fiction